2014
DOI: 10.1016/j.foreco.2014.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Forest harvest effects on mercury in streams and biota in Norwegian boreal catchments

Abstract: Forest harvesting practices can potentially increase mercury runoff from catchments. A paired catchment experiment was conducted in a boreal forest in southern Norway, to test effects of forest harvest operations on i) concentrations and fluxes of methylmercury (MeHg), total mercury (HgT), nutrients and dissolved organic matter (TOC), and on ii) MeHg bioaccumulation in stream foodwebs. Thirty percent of a catchment was harvested in winter time with snow cover but no soil frost, resulting in wheel tracks and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 66 publications
7
58
2
Order By: Relevance
“…In Table all studies reporting MeHg/DOC ratios after clear‐cutting are listed. Our reported average MeHg/DOC ratios for the 10 REFs (0.014 g g −1 above and 0.016 g g −1 below the ML) are similar to the average for Boreal coniferous forest reference stands (0.015 g g −1 , Table ) reported by Eklöf et al [] and de Wit et al []. In these two studies clear‐cutting only had minor effects on the MeHg/DOC ratio in the former and no effect in the latter study.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In Table all studies reporting MeHg/DOC ratios after clear‐cutting are listed. Our reported average MeHg/DOC ratios for the 10 REFs (0.014 g g −1 above and 0.016 g g −1 below the ML) are similar to the average for Boreal coniferous forest reference stands (0.015 g g −1 , Table ) reported by Eklöf et al [] and de Wit et al []. In these two studies clear‐cutting only had minor effects on the MeHg/DOC ratio in the former and no effect in the latter study.…”
Section: Discussionmentioning
confidence: 96%
“…In most of these studies, single or a few sites have been followed for several years (preharvest and postharvest) and reference stands have been used to correct for interannual variations. In de Wit et al [] the THg/DOC ratio decreased after harvest, but the period of pretreatment was only extended for 0.5 years and after that time the THg/DOC ratio reached a level similar to the REF. Only in one study [ Skyllberg et al , ] was the THg/DOC ratio reported to be significantly ( p < 0.05) higher in streams draining 1–4 year old CCs, as compared to streams draining REFs, but only at sites above the ML.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, De Wit et al. ). Because DOM quality controls its reactivity, influences ecosystem functions, and affects microbial food webs (Weishaar et al.…”
Section: Discussionmentioning
confidence: 99%